Impact Aerobic Toward Body Physiology and VO2max - Hutajulu, Pahala Tua; Mapandin, Wahida Yohanis; Mandosir, Yohanis Manfred (Universitas Negeri Semarang, 2020)
The purpose of study was to get the influence of aerobic using Yospan movement toward body physiology and VO2MAX. This research used a quasi-experimental study. The research design used The Randomized Pretest and Posttest. The research subjects were Yospan dancers located at the Sports Hall of Cenderawasih University. Data analysis used descriptive statistics, normality test and Paired samples test. The results of finding show that aerobic exercise with yospan movements affects an increase in pulse rate, body temperature, weight loss and VO2Max. This has implications for the level of physical fitness and the development of gymnastics activities with the preservation of local culture.